Pre‐release packing and chilling reduce host‐searching ability of the parasitoid Diachasmimorpha longicaudata used in the augmentative control of tephritid flies. Issue 5 (25th May 2020) - Cancino, Jorge; Mazariegos, Diana; Pérez, César; Ayala, Amanda; Díaz‐Fleischer, Francisco; Leal‐Mubarqui, Rubén; Angulo, Roberto
Abstract: Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) is a solitary parasitoid used in augmentative releases to control Tephritidae (Diptera) fruit flies of economic importance. Pre‐release process includes packing adult parasitoids in cages at high densities and expose them to a temperature of 2 ± 2 °C during 105 min. In this process, females' antennae may be damaged resulting in a reduction in their host‐searching ability and fecundity. Here we measured, for five consecutive days after chilling, the searching ability and fecundity of parasitoids with damaged (D) and undamaged (ND) antennae compared with parasitoids that were not chilled. Female individual responses to fruit infested by Anastrepha spp. was determined in an olfactometer. Latency in the response and latency in making a choice were recorded. Additionally, groups of 30 females were used to measure their ability to find hosts in infested fruit in the laboratory. Fecundity was determined by using artificial oviposition units with Anastrepha ludens (Loew) larvae. In the olfactometer test, ND had lower response than control females during the 1st and 2nd days after chilling. However, no difference in the response was observed between ND and D and the control females on the 5th day. Additionally, chilled females showed a longer latency of response to infested fruit than females of the control treatment when tested in groups. However, after a 24–48 h period, no difference between D and ND and control females was observed. Our results showed similar searching ability and fecundity among parasitoids of the three tested conditions at individual and at group levels. We conclude that pre‐release chilling reduces female searching ability only for the first 1–2 days after chilling. Abstract : Host‐searching ability and fecundity of the tephritid fruit fly parasitoid Diachasmimorpha longicaudata (Hymenoptera: Braconidae) were evaluated, after exposure to pre‐release packing and chilling. In an olfactometer, chilled female parasitoids showed a longer response time to infested fruit. After a 24–48 h period, chilled females gradually began to respond in a similar way as control females. We conclude that pre‐release chilling reduces female searching ability only for the first 1–2 days after chilling. Chilled females had no reduction in fecundity.